Estimated Value of Software Developer Productivity at the Software Implementation Stage Using Function Points - Asri Maspupah; Lukmannul Hakim Firdaus; Wendi Wirasta (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2023)
Most Software Development Processes (SDP) project failures occur due to errors in estimating cost, time, and effort during the planning phase. This happened because the planning carried out still relied on the intuition and experience of the programmer. One approach that can be taken to plan the right SDP is to know the value of SDP productivity. The focus of this research is to determine the value of productivity based on the differences in programmers’ skills. The case study is conducted to determine the productivity value of the web-based software that has been built, namely McDelivery. The productivity value is calculated based on the ratio of software size to the effort. Software size is obtained through the calculation of the Application Function Point Count (APFC). Meanwhile, the effort is obtained through expert judgment to determine the time needed by the development team at the junior, middle, and senior software developers to implement software functionality in person-day to the form of program code. The result shows that the productivity value of SDP is directly proportional to the level of ability of the programmers. These productivity values ​​can be used as a solution option to calculate the estimated time, cost, and even the availability of programmers that are adjusted to the conditions faced in planning software development